Exploring the expectations, needs and experiences of general practitioners and nurses towards a proactive and structured care programme for frail older patients: a mixed‐methods study. (5th March 2013) - Bleijenberg, Nienke; Ten Dam, Valerie Hester; Steunenberg, Bas; Drubbel, Irene; Numans, Mattijs E.; De Wit, Niek J.; Schuurmans, Marieke J.
Abstract: Aim: To report the expectations and experiences of general practitioners and practice nurses regarding the U‐CARE programme, to gain a better understanding of the barriers and facilitators in providing proactive, structured care to frail older people and to determine whether implementation is feasible. Background: Care for older patients with complex care needs in primary care is fragmented, reactive and time consuming. A structured, proactive care programme was developed to improve physical functioning and quality of life in frail older patients. Design: An explanatory mixed‐methods study nested in a cluster‐randomized trial. Methods: The barriers to and needs for the provision of structured, proactive care, and expectations regarding the U‐CARE programme were assessed with pre‐questionnaires sent to all participating general practitioners ( n  = 32) and practice nurses ( n  = 21) in October 2010. Postquestionnaires measured experiences with the programme after 5 months. Twelve months later, focus group meetings were conducted. Results: Practice nurses and general practitioners reported that it was difficult to provide proactive and structured care to older patients with multi‐morbidity, different cultural backgrounds and low socioeconomic status. Barriers were a lack of time and financial compensation. Most general practitioners and practice nurses indicated that the programme added value for the coordination of care and allowed them to provide structured care. Conclusion: This explanatory mixed‐methods study showed that general practitioners and practice nurses perceived the U‐CARE programme as feasible in general practice. A transition was made from reactive, ad hoc care towards a proactive and preventive care approach.